Pengaruh Motivasi Akademik terhadap Kematangan Karir - Vironica Andesta Meyshera; Stephani Raihana Hamdan (Bandung Conference Series: Psychology Science, 2023)
Abstract. Vocational High School students are classified as teenagers who have demands to be able to make decisions related to their future careers, while Vocational Schools are school institutions that have the goal of preparing graduates to have special skills and be absorbed in the world of work. In the learning process at Vocational Schools, the role of academic motivation is needed for students who play a role in fostering enthusiasm and passion for learning so that they are able to provide satisfactory results related to the goals of the vocational school itself (competent in the field of expertise and ready to go into the world of work). This study aims to examine the effect of academic motivation on the career maturity of students in grades XII and XIII at SMKNs throughout the city of Bandung, using a quantitative approach and causality research. The measuring instrument using the Academic Motivational Scale was constructed by Natalya referring to Valler's theory and on the basis of Ryan & Deci's Self Determination Theory. Career Maturity is measured using a career maturity instrument, which was constructed by Dewi Sartika based on Super theory. Data analysis used a simple regression test with 1,341 respondents. The results of the analysis show that the R Square value of academic motivation on career maturity is 0.158. This means that academic motivation has an influence on career maturity of 15.8%. Abstrak. Pelajar SMK adalah tergolong pada masa remaja yang memiliki tuntutan untuk mampu membuat keputusan terkait karir masa depanya, sementara SMK adalah institusi sekolah yang memiliki tujuan untuk mempersiapkan lulusannya memiliki keahlian khusus dan terserap di dunia kerja. Dalam proses belajar di SMK dibutuhkan peranan motivasi akademik pada siswa yang berperan dalam menumbuhkan semangat serta gairah untuk belajar sehingga mampu memberikan hasil yang memuaskan terkait tujuan dari sekolah kejuruan itu sendiri (kompeten dalam bidang keahlian dan siap turun ke dunia kerja). Penelitian ini bertujuan untuk menguji pengaruh motivasi akademik terhadap kematangan karir siswa kelas XII dan XIII SMKN se-Kota Bandung, dengan pendekatan kuantitatif dan jenis penelitian kausalitas. Alat ukur menggunakan Academic Motivational Scale dikonstuksi oleh Natalya mengacu pada teori Vallerand atas dasar Self Determination Theory Ryan & Deci. Kematangan Karir di ukur menggunakan instrumen kematangan karir, yang dikonstruksi oleh Dewi Sartika berlandaskan teori Super. Analisis data menggunakan uji regresi sederhana dengan responden berjumlah 1.341. Hasil analisis menunjukan nilai R Square motivasi akademik terhadap kematangan karir adalah 0,158. Artinya motivasi akademik memberikan kontribusi pengaruh terhadap kematangan karir sebesar 15,8%.